The Needs of Parents Who Have in Hospital Child - Nina Indriyawati; Bachtiar Bachtiar (Pusat Penelitian dan Pengabdian kepada Masyarakat, Poltekkes Kemenkes Semarang, 2012)
The research aim is to identify the needs of parents who have child in hospital. The research is descriptive. 30 parents who have child in Hospital ware involved in this reseaearch. Quesionaire about the needs of family was used ti cillect tha data. Descriptive statistic was used to analyse. The result shows that the most needs for parents are secure that have good medical care (Mean 3.37 ± SD 0.49), have to consult about child health progress (Mean 3.77 ± SD 0.43), get information about the result soon (Mean 3.97 ± SD 0.18), consult with doctor (Mean 3.73 ± SD 0.45), the medical team can understand parents’ feeling (Mean 4.00 ± SD 0.00). and permitted to stand by their child (Mean 3.93 ± SD 0.25).